2022
DOI: 10.1002/chem.202201557
|View full text |Cite
|
Sign up to set email alerts
|

Proteophenes – Amino Acid Functionalized Thiophene‐based Fluorescent Ligands for Visualization of Protein Deposits in Tissue Sections with Alzheimer's Disease Pathology

Abstract: Protein deposits composed of specific proteins or peptides are associated with several neurodegenerative diseases and fluorescent ligands able to detect these pathological hallmarks are vital. Here, we report the synthesis of a class of thiophene-based ligands, denoted proteophenes, with different amino acid side-chain functionalities along the conjugated backbone, which display selectivity towards specific disease-associated protein aggregates in tissue sections with Alzheimer's disease (AD) pathology. The se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(27 citation statements)
references
References 53 publications
1
21
0
Order By: Relevance
“…[122,175,176] In addition, due to minor chemical variations of the ligands, chemical determinants for achieving superior ligands for optical separation of distinct protein aggregates have been identified. [115,117,118,120,121,125,127] In 2015, Hermann and co-workers showed that p-FTAA (Figure 4A) binds to amyloid fibrils in a similar way as the conventional ligand CR. [122] By using the prion-forming domain of the fungal HET-s prion as a model, solid-state nuclear magnetic resonance analyses and molecular dynamics simulations showed that anionic side chains of p-FTAA interacted with complementary, regularly spaced lysine residues situated in well-accessible grooves along the HET-s fibrils (Figure 12A).…”
Section: Lcos: Binding Modes and Chemical Determinants For Superior L...mentioning
confidence: 94%
See 4 more Smart Citations
“…[122,175,176] In addition, due to minor chemical variations of the ligands, chemical determinants for achieving superior ligands for optical separation of distinct protein aggregates have been identified. [115,117,118,120,121,125,127] In 2015, Hermann and co-workers showed that p-FTAA (Figure 4A) binds to amyloid fibrils in a similar way as the conventional ligand CR. [122] By using the prion-forming domain of the fungal HET-s prion as a model, solid-state nuclear magnetic resonance analyses and molecular dynamics simulations showed that anionic side chains of p-FTAA interacted with complementary, regularly spaced lysine residues situated in well-accessible grooves along the HET-s fibrils (Figure 12A).…”
Section: Lcos: Binding Modes and Chemical Determinants For Superior L...mentioning
confidence: 94%
“…Such a dual staining protocol, allowing multiplex photophysical detection of distinct protein aggregates in brain tissue sections with AD pathology, was afforded when combining two proteophenes, HS-84-V-E (Figure 3E) and HS-169-V-V, with distinct amino acid side-chain functionalities along the conjugated thiophene backbone. [127] As the selectivity of the proteophenes towards AD associated pathological hallmarks was highly dependent on the chemical nature, as well as on the location of the amino acid functionality, a differential staining of Aβ or tau aggregates was observed. Characteristic lifetime distributions (600 and 1000 ps) from HS-84-V-E were observed from Aβ cored plaques, diffuse Aβ plaques, cerebral amyloid angiopathy (CAA) lesions and tau pathology, whereas longer decay times, 2000-3000 ps, associated with HS-169-V-V could only be detected from CAA lesions (Figure 7B).…”
Section: Fluorescence Lifetime Imagingmentioning
confidence: 99%
See 3 more Smart Citations